Blue luminescence of indium-doped ZnO thin films prepared by DC magnetron sputtering. Issue 1 (July 2021) - Sugianto, S; Nurilhilmah, N; Darsono, T; Sugiyanto, S; Aryanto, D; Isnaeni, I
Abstract: ZnO is an intrinsic semiconductor suitable for many optical applications. In this current study homemade DC magnetron sputtering was used to grow undoped ZnO and indium-doped ZnO (or IZO) thin films. The indium content was varied from a mole fraction ratio of In2 O3 were 0 at% to 6 at%. The structure of IZO films analyzed by X-ray diffraction (XRD), and the optical properties were carried out using UV-visible and photoluminescence (PL) spectroscopies. The XRD results demonstrated that IZO maintained a hexagonal wurtzite structure with a (002) preferential orientation. The optical band gap increased with an increase in indium doped concentration. The PL spectrum exhibits a broadband blue emission from IZO films centered at 440 nm (2, 82 eV), originating from the radiative recombination at the defect level. Interestingly, the intensity of blue emission increased with an increase in indium-doped concentration.